Dietary Supplementation of Silybum marianum Seeds Improved Growth Performance and Upregulated Associated Gene Expression of Muscovy Ducklings (Cairina moschata) - Osama El-Garhy; Fathia A. Soudy; Yousef M. Alharbi; Fahad A. Alshanbari; Mona S. Almujaydil; Raghad M. Alhomaid; Omar A. Ahmed-Farid; Shereen A. Mohamed; Hoda A. S. El-Garhy; Hassan Barakat; Ayman G. EL Nagar (MDPI AG, 2022)
The effect of feeding on diets supplemented with Silybum marianum L. dry seeds (SMS) on growth performance, mortality percentage, biochemical parameters, the expression profile of related genes, and genotoxic effect in Muscovy ducklings was evaluated during a brooding period of 4 weeks. Two hundred and forty one-day-old Muscovy ducks were randomly assigned to four treatment groups (60 ducklings/group), the first group fed on basal diet with no additives (control), and the second (4 g kg−1), third (8 g kg−1), and fourth (12 g kg−1) groups fed the basal diet supplemented with 0, 4, 8, and 12 g kg−1 diet SMS, respectively. A substantial improvement in live body weight (LBW), body weight gain (BWG), and growth rate (GR), and a decrease in feed conversion ratios (FCR) and mortality rate were shown in ducks fed a diet supplemented with either 8 g kg−1 or 12 g kg−1 SMS compared to the other groups. Relevant improvements in liver function, oxidative stress markers, purinergic cell energy, and brain appetite were recorded on ducklings fed diets supplemented with SMS. Moreover, diets which included 8 or 12 g kg−1 SMS positively upregulated the expression of growth hormone gene (GH) and antioxidant genes (SOD1, SOD2, and CAT). These results are consistent with the increase in liver activity SOD and CAT enzymes, resulting in less DNA fragmentation. Consequently, all the aforementioned improvements in biochemical parameters and gene expression profiling may explain the superiority of the treated ducklings compared with the control group. Conclusively, the SMS could be used as a natural feed additive to promote health status and improve the growth performance of small grower ducks during the brooding period.